Schleichera oleosa (Molk.)Oken Callus Induced BAP and 2,4 D In vitro - Ruri Siti Resmisari; Azizatur Rahmah (El-Hayah, 2022)
Schleichera oleosa (Lour.) Oken is a plant that it can used as drug candidate. S. oleosa has several health benefits including as anti-cancer, anti-oxidant, and anti-microbial. One of technique for increasing the secondary metabolite in S. oleosa (Lour.) Oken is callus culture. This study is an experimental research using Factorial Completely Randomized Design (CRD). This study consist of 2 factors are  Benzyl Amino Purin (BAP) and 2,4-Dichlorophenoxyacetic Acid (2,4-D) with various concentrations. Based on the result of callus induction of S. oleosa (Lour.) Oken, it gives some different effect for the variable. The day of emerging callus and weight of callus give the optimum result at 2 mg/L 2,4-D + 0,5 mg/L BAP for 32 Day After Planting and 1,1458 grams. Besides, the percentage of callus formation at 1 mg/L 2,4-D + 0,5 mg/L BAP for 83,33%.